Use of Mamta Card by Pregnant and Lactating Mothers attending Village Health and Nutrition Days in Rural Area of Valsad, Gujarat - Bhavesh R Bariya; Mitali G Patel; Darshan K Mahyavanshi; Sunil Nayak (Medsci Publications, 2019)
Introduction: The MCP card is a tool for pregnant women, young mothers and family members to learn understand and achieve good health practices. It contains information about antenatal care, danger signs, preparation for delivery, newborn care, immuniza- tion and growth chart. Objective: The study conducted to assess the use of MCP card by beneficiaries attending VHND sessions in rural Valsad. Methodology: It was a cross sectional study. Total 43 pregnant and lactating mothers were interviewed to know the use of MCP card by them. Their knowledge was checked by asking open  ended questions about information provided in MCP card. Results: 65.1% mothers had read the MCP card. 86.5% of the mothers could tell at least one use of Mamta card of which major- ity (86.49%) used it as immunization record of the child while 67.57% used it for information. 88% mothers brought the card at every visit to the health center. Mothers were quite aware about emergency signs, but knowledge about vaccination, growth moni- toring, hygiene and various government schemes was poor. Conclusion: Effective use of MCP card is still lacking by benefici- aries. Advocacy by health care providers may improve the knowl- edge of beneficiaries about various health information provided already in MCP card.